Drying behaviour and microbial load after water damage. Issue 1 (11th April 2016) - Zegowitz, Andreas; Renzl, Anna; Hofbauer, Wolfgang; Meyer, Joerg; Kuenzel, Hartwig
Abstract : Purpose: – The water damage in buildings because of leaking pipes and increasingly because of floods and severe weather require professional help. Methods for improved repair and remediation techniques have to be developed. The water damage in buildings because of leaking pipes and increasingly because of floods and severe weather require professional help. Methods for improved repair and remediation techniques have to be developed. The paper aims to discuss these issues. Design/methodology/approach: – Therefore, large scale laboratory tests with four rooms, each with three types of masonry walls (Figure 2 and Plate 1) and typical floors for intermediate storeys with insulation were performed within a climate simulator. Artificial water damage was provoked through watering the floors, and the dispersion of water in the floors and the rising damp in the walls was measured. In the follow-up to the watering of the floors, a company specialized in drying wet buildings, installed systems for under floor drying and wall drying. Findings: – The drying process of the different components and layers of the floor construction and walls was monitored by a measuring system with more than 300 sensors for moisture content, relative humidity and temperature accompanied by thermography and demonstrated so the advantages and disadvantages of the different tested drying systems. After providing an initial contamination that is typical for construction sites, the microbial load (mould infestation) within the wet components was monitored at different times by experienced biologists. So after three weeks under floor drying no mould growth could be asserted but more bacteria than expected were found. Originality/value: – The aim of the research was to gain more confidence in selecting appropriate drying procedures and systems in order to identify the right moment for terminating the drying process. A further intent was to acquire data for computer simulations.